Body composition, eating habits and risk factors for the development of eating disorder in female elite athletes - Nenad Ponorac; Mira Spremo; Tanja Šobot (University of Banja Luka, Faculty of physical education and sport, 2018)
The number of women who actively participate in sports has drastically increased in the last few decades, which is a trend followed by many health benefits and serious harmful health side effects as well. The Female Athlete Triad stands out among these as a condition which includes eating disorders, menstrual disorders and osteoporosis. Eating disorders are the first link to which all other disorders are later attached, while the risk for their development remains undetected despite the specificities of certain sports. They often develop out of eating restrictions (diets) or out of an unhealthy eating habit. The aims of this paper were to detect the risks for the development of eating disorder by 1) determining body composition parameters and harmful eating habits and 2) identifying risk factors suggested by American Academy of Family Physicians. The sample of examinees was comprised of elite female athletes (111) divided into three groups (sports that use a ball, dance and athletics), each with different risks for the development of eating disorder. The control group (27) consisted of non-athletic female students. The examinees were measured body composition, BMI and they answered a questionnaire which estimates risks for the development of eating disorder in primary health care. Based on the answers to screening questions and eating habits, the results showed significantly bigger risks for the development of eating disorder in the athletes' group, compared to the control group. Low BMI of less than 18.5, as direct criteria for energy deficiency, was also more present (p<0,05) in the athletes' group. Therefore, based on body index values and key screening questions, we conclude that active participation in sports carries a bigger risk for the development of eating disorder.